Mobile learning utilization: a proposed model to investigate an important predictors of mobile learning utilization and measure the role of behavioral intention as a mediator variable - Mohammad Al Tabib, Shaima’a; Mohd Daud, Shaffe; Mahmud, Rosnaini; Ayub, Ahmad Fauzi; Moustafa Qoussini, Alla Edein (American-Eurasian Network for Scientific Information, 2016)
Mobile learning is the extension of e-learning. Mobile learning becomes an important tool for successful learning, since an opportunity to learn anywhere and at any time. The research objective is to examine the possibility of utilizing mobile learning and study important factors that influence using mobile learning with focus on higher education students in Oman. The effectiveness of using mobile learning needs to achieve a positive behavioral intention to use it. However, much of the researches regarding using mobile learning seem to suffer from several shortcomings. On top of that, there is no common theoretical foundation on special model for using mobile learning. This study was based on a quantitative descriptive design with a sample size of 380 undergraduate students in the third-fourth years at Sultan Qaboos University (SQU). The sample was selected based on the proportional stratified and cluster sampling technique. The main instrument used was a questionnaire which was adapted from previous studies and whose content validity was checked by a panel of experts. A pilot study was conducted on 40 students to assist the reliability of the instrument which ranged in value from 0.822 to 0.949 on Cronbach’s alpha. The modified utilization framework is a combination between the Unified Theory of Acceptance and Use of Technology (UTAUT), Mobile Learning acceptance Model (MLAM), and Liew’s Model. Further, this study introduces behavioral intention as a mediator variable that is believed to mediate the relationship between the selected factors and mobile learning utilization. The results from AMOS statistical analysis revealed a model that predicts the utilization of mobile learning among the undergraduates and which explained 50% of perceived mobile learning utilization and 26% of behavioral intention towards mobile learning utilization. Several implications were also drawn from the findings of this research. Finally, the proposed model is a definitive model that synthesizes what is known, and is likely to be a useful model that provides knowledge to guide future research in related fields.